Charting new pathways to C4 rice (IRRI, 2007)
This book describes the alternative ways of achieving C4 photosynthesis in rice. Featuring contributions from leading experts, case studies are used to present views on how C4 rice might be constructed and applied, along with the socioeconomic implications that it entails. Ultimately, readers will be better informed about this highly relevant and timely topic of improving rice yield in a global environment grappling with unpredictable climate change.